PENGARUH KETEKUNAN BELAJAR, KECERDASAN EMOSIONAL, PERHATIAN ORANG TUA, TEMAN SEBAYA DAN KEMANDIRIAN BELAJAR TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 SITIUNG - Karel Sumayasa; Jimi Ronald; Mareta Kemala Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze: 1) the influence of persistence in studying on learning motivation, 2) the influence of emotional intelligence on learning motivation, 3) the influence of parental attention on learning motivation, 4) the influence of peer learning on learning motivation, 5) the influence of learning independence on learning motivation. The type of research used in this research is associative research. When this research was conducted in July 2025. The population in this research was all class x students in economics subjects at SMAN 1 Sitiung. The sample in this study was 149 people. The sampling technique was Random Sampling and the data analysis technique used was descriptive analysis and inductive analysis, with the help of the Eviews and SPSS version 21.0 programs. The results of the research show that 1) there is an influence of study persistence on learning motivation with a coefficient value of - 0.418 with a calculated t value > t table (-5.064 <1.65558) and a significant value of 0.000 < 0.05, 2) the influence of emotional intelligence on learning motivation with a coefficient value of 0.343 with a calculated t value < t table (3.229 > 1.65558) and a significant value of 0.002 > 0.05, 3) the influence of parental attention on learning motivation with a coefficient value of -0.354 with a calculated t value > t table (-0.458 <1.65558) and a significant value of 0.000 < 0.05, 4) the influence of peers studying on learning motivation with a coefficient value of 0.406 with a calculated t value < t table (4.317 < 1.65558) and a significant value of 0.000 > 0.05, 5) the influence of learning independence on learning motivation with a coefficient value of -0.094 with a calculated t value > t table (-1.109 > 1.65558) and a significant value of 0.269 < 0.05.